Answer:
(x, y ) = (-4.5, -10)
Explanation:
2x - 3y = 21 ------- eq 1
- 6x + 2y = 7 -------- eq 2
Part 1 : Eliminating the x term
Steps: Multiply eq 1 with 6 and multiply eq 2 with 2 so that value of x becomes equal in both equations
6(2x - 3y) = 21 × 6 ----- 12x - 18y = 126 -----eq 3
2(- 6x + 2y) = 7 × 2---- - 12x + 4y = 14 -----eq 4
The values of x are equal but of opposite sign so we should add the two equaitons to eliminate x
Adding eq3 + eq4:
12x - 18y + ( -12x + 4y ) = 126 + 14
12x - 18y - 12x +4y = 140
-14y = 140
y =
y = - 10
Part 2: Eliminating the y term:
Steps: Mulitply eq 1 with 2 and eq 2 with 3 so that the value of y becomes equal in both equations
2(2x - 3y) = 21 × 2 ------- 4x - 6y = 42 ------- eq 5
3( -6x + 2y ) = 7 × 3 ----- -18x + 6y = 21 ----- eq 6
The values of y are equal but of opposite signs so we should add the equation to eliminate y
4x - 6y + (-18x + 6y) = 42 + 21
4x - 6y - 18x + 6y = 63
-14x = 63
x =
x = - 4.5
Part 3: Choosing the y elimination method to solve the system:
By putting this value of x in eq 1
2x- 3y = 21
2 (-4.5) - 3y = 21
-9 - 3y = 21
-3y = 21 + 9
-3y = 30
y = - 10
Proof:
2x - 3y = 21
2 (- 4.5) - 3(-10) = 21
-9 + 30 = 21
21 = 21